Antegrade insertion of a retrograde intramedullary femoral nail for treatment of a subtrochanteric pathological femoral shaft fracture in a patient with pre-existing coxa vara - Ravi Patel, MBBS; Daniel Omonbude, MBBS, MRCSEd, FRCS (Tr & Orth); Victor Lu, MB, BChir; Majeed Shakokani, MBBS, MRCS, FRCS (Tr & Orth) (Radiology Case Reports, 2022)
Objective: We report the unorthodox use of a retrograde intramedullary nail via antegrade technique for the treatment of a subtrochanteric pathological femur fracture in the presence of significant coxa vara. No similar use has been documented previously in literature. Methods: A standard approach to the proximal right femur was performed and standard antegrade technique used to introduce a guide wire into the proximal femur after which the femoral shaft was reamed. A 38-cm long 10 mm diameter retrograde nail was attached to the retrograde insertion and targeting device as if to perform a left sided retrograde femoral nailing. The nail was then inserted antegrade into the proximal right femur and locked. Results: The patient made a good recovery without complications and was followed up regularly at the clinic until complete healing of the fracture. Conclusion: We believe that a retrograde intramedullary nail inserted antegrade, enabling proximal locking with screws passing into the femoral head, provides a mechanically sound fixation of a subtrochanteric fracture, where a reduced neck-shaft angle precludes the use of a standard cephalo-medullary nail.